2022
DOI: 10.1177/27527263221107718
|View full text |Cite|
|
Sign up to set email alerts
|

Fostering noticing in prospective teachers through a video-based course: Results of an intervention study from China

Abstract: Teacher noticing of student mathematics thinking, an essential professional competency, has not been sufficiently investigated in China. In this paper, based on four video clips, we combined the frameworks of Stockero et al. and Jacobs to analyze the characteristics and changes of 19 prospective teachers’ (PTs) noticing under the intervention of the course “Mathematics Teaching Theory in Middle School.” The results showed that (1) the agent of noticing shifted from teachers and mathematical content to students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This indicates that PSTs developed enhanced skills in recognizing critical events related to mathematical modelling. These results align with previous studies conducted by Qi et al (2022) and Stockero et al (2017) in a general context. Our previous study observed a significant increase in the percentages of noticing related to analyzing student math learning and math interaction.…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that PSTs developed enhanced skills in recognizing critical events related to mathematical modelling. These results align with previous studies conducted by Qi et al (2022) and Stockero et al (2017) in a general context. Our previous study observed a significant increase in the percentages of noticing related to analyzing student math learning and math interaction.…”
Section: Discussionsupporting
confidence: 93%
“…Although limited prior literature discusses using web-conferencing tools such as Skype, Microsoft Teams, and FaceTime to collect data, many researchers have used other online communication technologies during data collection, such as annotation systems, instant messaging software, emails, and chat rooms. These digital tools have demonstrated their effectiveness for researchers in recording real-time verbal and non-verbal interaction that involves videos, audio, written text, and interviews, which can capture the lived experience of students (Archibald et al, 2019; Howlett, 2022; Qi et al, 2022). For example, Hwang et al (2011) found that annotations play a more important role in learning achievement than homework since learners can actively and voluntarily create texts and present solutions.…”
Section: Introductionmentioning
confidence: 99%